Experimental and numerical analysis of pGFRP and wood cross-arm in latticed tower: a comprehensive study of mechanical deformation and flexural creep - Amir Abd Latif; Mohamad Ridzwan Ishak; Muhammad Rizal Razman; Noorfaizal Yidris; Mohamed Yusoff Mohd Zuhri; Muhammad Asyraf Muhammad Rizal; Zuliskandar Ramli (Scientific Reports)
Abstract The adoption of pultruded glass fibre-reinforced polymer (pGFRP) composites as a substitute for traditional wooden cross-arms in high transmission towers represents a relatively novel approach. These materials were selected for their high strength-to-weight ratio and lightweight properties. Despite various studies focusing on structures improvement, there still have a significant gap in understanding the deformation characteristics of full-scale cross-arms under actual operational loads. Existing study often concentrate on small coupon scale and laboratory condition, leaving a gap in understanding how the cross-arm behavior in full-scale acting on actual weather condition. This study aims to investigate the load-deflection and long-term creep behavior of a pGFRP cross-arm installed in a 132 kV transmission tower. The pGFRP cross-arm was load-tested on a customized rig in an open environment. Using the cantilever beam concept, deflection was analyzed and compared to wood cross-arms. Finite element analysis validated results, and long-term deformation under high-stress loads was assessed. The pGFRP cross-arms showed lower deflection at working loads compared to Balau wood, due to the latter’s higher elastic modulus and flexibility specifically at Point Y3, the critical issues necessitated reinforcement strategies. pGFRP cross-arms withstood higher bending stress, showing 32% less deflection under normal conditions and 15% less under broken wire conditions than Balau wood. Additionally, the creep strength of wood was 34% lower than that of pGFRP cross-arms. Besides that, the pGFRP cross-arm have highest elastic modulus than Balau-wood, shows that the composite cross-arm have better structural strength, resisting deformation and higher flexibility materials. Finite element analysis (FEA) confirmed these results with the relative error between them less than 1%. Consequently, the investigation into pGFRP cross-arm deformation behavior in this paper serves as a foundational framework for future research endeavors specifically for high transmission tower and other structural application.